Asianism and the politics of regional consciousness in Singapore - Yew, Leong, 1969- (London : Routledge, 2014)
'Over the last two decades, Singapore has undergone a substantial degree of'Asianization'. Apart from participating in the Asian values debate of the 1990s, re-visioning itself as'New Asia' and a global-Asian hub, and establishing Asian identities for the commodities it consumes and produces, Singapore has also repurposed its modernity, cultures, and ethos along similar regionalist precepts. However, even in recent times, Singapore continues to vacillate ambivalently between identifying with and differentiating itself from Asia. Responding to the challenges Singapore faces in coming to terms with its Asian identity, this book examines the complex cultural, social, and political underpinnings that have shaped Singapore's mainstream discourse in Asia. Indeed, it argues that its legacy as a colonial port city, the exigencies of managing the post-independence nation state, and the larger forces of imperialism and capitalism all contribute to its politics of Asianism. Taking a thoroughly interdisciplinary approach, that spans history, cultural studies, postcolonialism, and cultural geography, Leong Yew reveals how Asia has been used to narrate Singapore's beginnings, revalidate Singaporean ethnic culture and to consolidate its practices of consumption and commodification'--
Includes bibliographical references and index.
Keywords: Regionalism -- Political aspects -- Singapore; Regionalism -- Political aspects -- Asia; National characteristics, Singaporean; Singapore -- Relations -- Asia; Asia -- Relations -- Singapore; Singapore -- Politics and government